2007
DOI: 10.1111/j.1365-2389.2006.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and nitrogen stocks in relation to organic matter fractions, aggregation and pore size distribution in no‐tillage and conventional tillage in northern France

Abstract: The magnitude of and mechanisms for long-term differences in soil organic matter stocks under no-tillage and conventional tillage are still relatively poorly known. We quantified differences in total C and N stocks after 32 years of no-tillage (NT) and conventional tillage (CT) in plots with a long-term cultivation history before differentiation and the same annual C and N returns to the soil. The role of physical protection of organic matter (OM) in these stock differences was further investigated by examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 45 publications
5
37
0
6
Order By: Relevance
“…Data from long-term trials summarised by of sampling not given). Similarly in France, measurements made on the Boigneville long-term field trial (32 years) have shown that the difference between C stocks in ploughed and no-till treatments within the 0-28 cm depth during a 32-year period was +5.2 Mg C ha -1 in favour of no-till (Oorts at al., 2007a) which is equivalent to 162 kg C ha -1 yr -1 . In a semi-arid area in northern central Spain the soil carbon accumulation to a depth of 30 cm after 10 years of no-till was 25% higher than after mouldboard ploughing (Sombrero and De Benito, 2010).…”
Section: Sequestration Of Carbonmentioning
confidence: 99%
“…Data from long-term trials summarised by of sampling not given). Similarly in France, measurements made on the Boigneville long-term field trial (32 years) have shown that the difference between C stocks in ploughed and no-till treatments within the 0-28 cm depth during a 32-year period was +5.2 Mg C ha -1 in favour of no-till (Oorts at al., 2007a) which is equivalent to 162 kg C ha -1 yr -1 . In a semi-arid area in northern central Spain the soil carbon accumulation to a depth of 30 cm after 10 years of no-till was 25% higher than after mouldboard ploughing (Sombrero and De Benito, 2010).…”
Section: Sequestration Of Carbonmentioning
confidence: 99%
“…Ces re´sultats sont comple´te´s par les observations de Oorts et al (2006aOorts et al ( , b, 2007 sur ce meˆme dispositif concernant l'analyse des me´canismes susceptibles d'expliquer les diffe´rences d'e´volution des compartiments de la matie`re organique sous l'influence des traitements applique´s. Ils montrent ainsi que l'horizon de surface du sol sous semis direct pre´sente des stocks de carbone et d'azote respectivement supe´rieurs de 5 a`15% et de 3 a1 0% a`ceux mesure´s dans l'horizon laboure´correspon-dant, avec des diffe´rences entre traitements qui ne sont pas toujours statistiquement significatives.…”
Section: Discussionunclassified
“…La pre´sentation a trois objectifs. (Balesdent et al 1990;Wylleman et al 2001 ;The´venet et al 2002 ;Oorts et al 2006aOorts et al , b, 2007. Le sol est un sol brun calcique sur loess (Haplic Luvisol): les principales caracte´ristiques de l'horizon laboure´au de´but de l'expe´rimentation e´taient les suivantes : argile : 22% ; limon (2Á50 mm) 70% ; sable : 8% ; carbone organique : 10 mg g (1 ; N total Kjeldhal : 1,2 mg g (1 ; CEC : 0,125 mmol c g (1 ; pH 6,1.…”
unclassified
“…Often, carbon storage and biodiversity protection under conservation systems are mentioned as important ecosystem services for which farmers could be paid. Research in the last decade has consistently shown that carbon storage gains in conservation systems are lower than was anticipated two decades ago and are generally well below 1 t C ha −1 yr −1 (Oorts et al, 2007;Angers and EriksenHamel, 2008;Christopher et al, 2009;Eagle et al, 2012;Govers et al, 2013). Furthermore, paying farmers to store carbon would only be viable at much higher carbon prices than the current market prices, which are around USD 10-15 t −1 (Grace et al, 2012;Govers et al, 2013).…”
Section: Why Then Is Soil Conservation Not More Generally Adopted?mentioning
confidence: 99%